Effects of hCG administered 5 or 7 days after the onset of induced estrus on luteal morphology and function in seasonally anovular dairy goats - Rodrigues, Juliana Nascimento Duarte; Guimarães, José Domingos; Rangel, Paulo Sergio Cerqueira; Oliveira, Maria Emilia Franco [UNESP]; Brandão, Felipe Zandonadi; Bartlewski, Pawel Mieczyslaw; Fonseca, Jeferson Ferreira (Elsevier, 2025)
The objective was to evaluate the effects of intramuscular (i.m.) human chorionic gonadotropin (hCG) administered on day 5 (D5) or day 7 (D7) after estrus (D0) on luteal structures (number, area, vascularization, and progesterone secretion) and pregnancy rates in estrus-induced dairy goats during the non-breeding season. Thirty-four Alpine goats received intravaginal sponges containing medroxyprogesterone acetate for 6 days and a single i.m. injection of 200 international units (IU) of equine chorionic gonadotropin (eCG) plus 37.5 micrograms (µg) of d-cloprostenol 24 hours before sponge removal. All exhibited estrus and were mated by fertile bucks. Goats were randomly assigned to hCG-5 (300 IU on D5; n = 12), hCG-7 (300 IU on D7; n = 11), or controls (n = 11). Transrectal ovarian ultrasonography and blood sampling were performed on D5, D7, D10, D13, D17, and D21, with pregnancy diagnosis on D60. hCG treatment did not affect pregnancy rates. Accessory corpora lutea (aCL) appeared in 66.6 % (hCG-5) and 90.9 % (hCG-7) (P > 0.05). Total luteal area in hCG-7 was greater (P < 0.05) than in controls from D10 to D21. The mean original corpora lutea (oCL) area in hCG-7 was largest (P < 0.05) on D10. High-velocity Doppler area (HVDA) of aCL was greater (P < 0.05) in hCG-5 compared with hCG-7 on D13. Plasma progesterone (P4) concentrations were higher (P < 0.05) in hCG-7 than in controls from D10 to D21. Although hCG administered on D5 or D7 transiently enhanced luteal function and vascularization, it did not improve pregnancy outcomes in seasonally anovular dairy goats.
Keywords: Corpus luteum; Goat; Human chorionic gonadotropin; Progesterone; Ultrasonography